2008
DOI: 10.1016/j.drugalcdep.2008.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Using a factor mixture modeling approach in alcohol dependence in a general population sample

Abstract: Alcohol dependence (AD) is a complex and heterogeneous disorder. The identification of more homogeneous subgroups of individuals with drinking problems and the refinement of the diagnostic criteria are inter-related research goals. They have the potential to improve our knowledge of etiology and treatment effects, and to assist in the identification of risk factors or specific genetic factors. Mixture modeling has advantages over traditional modeling that focuses on either the dimensional or categorical latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 44 publications
4
33
1
Order By: Relevance
“…A two-class (low endorsement vs. high endorsement for abuse and dependence criteria), single factor model (i.e., single dimension within each class) was found in the first application of this type of model to DSM-IV abuse and dependence criteria (Muthén, 2006). The two latent classes were differentiated primarily by probability of impairment in social and work activities and did not correspond to the DSM-IV alcohol abuse and dependence categories, which is also consistent with Kuo et al (2008) and McBride et al (2013) who found similar dimensionality with 3-classes.…”
Section: Introductionsupporting
confidence: 80%
“…A two-class (low endorsement vs. high endorsement for abuse and dependence criteria), single factor model (i.e., single dimension within each class) was found in the first application of this type of model to DSM-IV abuse and dependence criteria (Muthén, 2006). The two latent classes were differentiated primarily by probability of impairment in social and work activities and did not correspond to the DSM-IV alcohol abuse and dependence categories, which is also consistent with Kuo et al (2008) and McBride et al (2013) who found similar dimensionality with 3-classes.…”
Section: Introductionsupporting
confidence: 80%
“…Based on the URS, the parallel shift of classes with respect to criterion endorsement probabilities indicates that classes differ in terms of quantity (i.e., severity), rather than quality (i.e., patterns). This is in line with previous LCA studies on alcohol (Bucholz et al, 1996;Kuo, Aggen, Prescott, Kendler, & Neale, 2008;Muthén, 2006) and other substance use disorders (Agrawal, Lynskey, Madden, Bucholz, & Heath, 2007;Chung & Martin, 2005;Grant et al, 2006). Based on the RS, however, a qualitative interaction between abuse, dependence and class membership emerged.…”
Section: Discussionsupporting
confidence: 76%
“…The severity of their alcoholism, co-morbid psychiatric disorders, and abuse of substances in addition to alcohol is similar to the more severe subtypes of alcohol dependent individuals identified by latent class analyses of interviews with large epidemiological samples (Kuo et al, 2008;Moss et al, 2007). According to Moss and colleagues analysis, the subtypes similar to our subjects account for about 30% of individuals meeting DSM-IV criteria for alcohol dependence in a population-based household survey.…”
Section: Discussionmentioning
confidence: 58%